2014
DOI: 10.1111/infa.12056
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Confidence Cues Increases during the Second Year of Life

Abstract: We investigated the emergence in infancy of a preference to imitate individuals who display confidence over lack of confidence. Eighteen‐ and 24‐month‐olds (N = 70) were presented with an experimenter who demonstrated the use of several objects accompanied by either nonverbal expressions of confidence or lack of confidence. At 24 months, infants were more likely to imitate the actions when demonstrated by a confident experimenter than by an unconfident experimenter; 18‐month‐olds showed no such preference. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…Eighteenmonth-olds might be early enough in the process of learning to exchange information that they have no default assumptions about others. Of course, between 18 and 24 months, toddlers also develop higher sensitivity to confidence cues, which they rely on in deciding whom to trust (Brosseau-Liard & Poulin-Dubois, 2014). It is possible that children see speakers who ask questions as being less confident than speakers who make statements, making them both unreliable.…”
Section: This Finding Corroborates and Extends Work By Brooker Andmentioning
confidence: 99%
“…Eighteenmonth-olds might be early enough in the process of learning to exchange information that they have no default assumptions about others. Of course, between 18 and 24 months, toddlers also develop higher sensitivity to confidence cues, which they rely on in deciding whom to trust (Brosseau-Liard & Poulin-Dubois, 2014). It is possible that children see speakers who ask questions as being less confident than speakers who make statements, making them both unreliable.…”
Section: This Finding Corroborates and Extends Work By Brooker Andmentioning
confidence: 99%
“…Confidence is certainly one clue to the quality of a source’s knowledge, and one that children use. A sensitivity to confidence in demonstrations of object use emerges early in development, increasing dramatically during the second year of life (Brosseau-Liard & Poulin-Dubois, 2014). Even before rich language processing is available, non-verbal confidence is monitored as a way of judging the informativeness of others’ actions.…”
Section: Developmental Challengesmentioning
confidence: 99%
“…Results revealed that infants were able to detect the unreliable emoter, as shown by their increased latency to inspect the content of the box over trials. In addition to emotional cues, infants have also been shown to rely on the conventionality (Zmyj, Buttelmann, Carpenter, & Daum, 2010) as well as the confidence (Birch, Akmal, & Frampton, 2010;Brosseau-Liard & Poulin-Dubois, 2014) conveyed by the informant. Similarly, research has shown that infants are less likely to imitate the novel actions of an informant who displays unreliable emotional cues (Poulin-Dubois, Brooker, & Polonia, 2011).…”
mentioning
confidence: 99%